2014
DOI: 10.1016/j.neo.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Study Combining the DNA Repair Inhibitor Dbait with Radiotherapy for the Treatment of Melanoma

Abstract: Melanomas are highly radioresistant tumors, mainly due to efficient DNA double-strand break (DSB) repair. Dbait (which stands for DNA strand break bait) molecules mimic DSBs and trap DNA repair proteins, thereby inhibiting repair of DNA damage induced by radiation therapy (RT). First, the cytotoxic efficacy of Dbait in combination with RT was evaluated in vitro in SK28 and 501mel human melanoma cell lines. Though the extent of RT-induced damage was not increased by Dbait, it persisted for longer revealing a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 48 publications
5
58
0
Order By: Relevance
“…This pharmacological form called AsiDNA (or DT01), has been tested in phase I clinical trial on melanoma in association with radiotherapy. Two studies show the selective increase of cancerous cells sensitization [39,40]. Preclinical studies showed a chemo-sensitization of metastatic colorectal and liver cancers with AsiDNA [41].…”
Section: Targeting Dna-pk With Inhibiting Moleculesmentioning
confidence: 99%
“…This pharmacological form called AsiDNA (or DT01), has been tested in phase I clinical trial on melanoma in association with radiotherapy. Two studies show the selective increase of cancerous cells sensitization [39,40]. Preclinical studies showed a chemo-sensitization of metastatic colorectal and liver cancers with AsiDNA [41].…”
Section: Targeting Dna-pk With Inhibiting Moleculesmentioning
confidence: 99%
“…11). We demonstrated that local administration of DT01 by intratumoral injection in association with radiotherapy increases survival of xenografted human melanoma models (13). However to date, the efficacy of systemic administration of DT01 in association with chemotherapy has not been investigated.…”
Section: Introductionmentioning
confidence: 95%
“…We previously showed Dbait to be effective in combination with radiotherapy on several radio-resistant tumors, both in vitro and in vivo (8,(11)(12)(13). Furthermore, studies on an intestinal tumor rodent model revealed that oral administration of Dbait, in association with the chemotherapy agents 5-fluorouracil and camptothecin leads to increased chemosensitization of intestinal tumors and to a low systemic exposure (14).…”
Section: Introductionmentioning
confidence: 99%
“…AsiDNA acts by hijacking and hyper-activating PARP1 (13) and the DNA-dependent protein kinase (DNA-PK) (14) which modify the chromatin and consequently inhibit the recruitment of many proteins involved in the HR and NHEJ pathways at the damage sites (14). This strategy sensitizes tumors to DNA damaging therapies such as radiotherapy and chemotherapy (15)(16)(17)(18). The first-in-human phase I trial, combining AsiDNA to radiotherapy to treat patients with skin metastases from melanoma showed encouraging results, with 30% of complete responses (19).…”
Section: Introductionmentioning
confidence: 99%